TRADISI NYAER KITAB KIFAYAT AL-MUHTAJ SEBAGAI MEDIA DAKWAH DI LOMBOK - Acim, Subhan Abdullah; Ahyar, Ahyar (JURNAL PENELITIAN KEISLAMAN, 2011)
he study explores the origin of nyaer tradition in Lombok and the reasons the people hold it during Islamic celebrations. Specifically, the study attempts to uncover the values of education of the tradition as means of propagating Islam. The study finds that the nyaer tradition of the book of Kifayah al-Muhtaj began since the coming of Islam into the island and has been maintained from the earlier generation up to the present. The common reasons for upholding nyaer is because it is seen as medium through which the continuity of generations is assured, religious values are preserved and Islamic propagation is established. As a means of disseminating Islam, the book promotes Islamic messages such as consistence and mutual respect among people. The book also fosters charity and the spirit of love for the Prophet and strengthens Islamic unity. For Muslims in Lombok, the book plays a pivotal role in bringing the people into the realization of Islamic teachings.